AN OBSERVATION STUDY FOR THE OUTPUT VOLTAGE AND ELECTRIC CURRENT IN THE USED MAINTENANCE FREE ACCUMULATOR AFTER ADD BY SILVER NANOPARTICLES IN AGNO3 SOLUTION - Riksa Ginanjar , Wipsar Sunu Brams Dwandaru (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2018)
Abstrak Penelitian ini bertujuan untuk i) mengetahui pola tegangan keluaran aki maintenance free bekas yang ditambahkan nanopartikel perak pada rangkaian tertutup, ii) mengetahui pola arus keluaran aki maintenance free bekas yang ditambahkan nanopartikel perak pada rangkaian tertutup. Penelitian ini dimulai dengan membuat nanopartikel perak dalam bentuk larutan AgNO3 3 mM untuk setiap penelitian yang dilakukan. Selanjutnya, menguji karakteristik absorbansi larutan nanopartikel perak dengan uji Spektrofotometer UV-Vis. Kemudian, 3 mL larutan nanopartikel perak dengan nilai absorbansi 3,187 ditambahkan ke dalam aki maintenance free bekas. Pengukuran tegangan dan arus keluaran aki maintenance free bekas dilakukan selama 240 menit dengan pemakaian 2 lampu LED. Data hasil penelitian ini disajikan dalam bentuk grafik yang selanjutnya dianalisis menggunakan fitting Origin untuk dicari fungsi dari tegangan dan arus keluaran aki maintenance free bekas tersebut. Berdasarkan hasil yang diperoleh, pola tegangan dan arus keluaran aki maintenance free bekas yang ditambah nanopartikel perak 3 mM berbentuk fungsi polinomial orde 3. Fungsi karakteristik tegangan keluaran minggu 1: y = 8,507 + 0,0021x + (1,01E-05)x2 + (-2,1E-08)x3, minggu 2: y = 8,694 - 0,0013x + (5,6E-06)x 2 + (-1,8E-08)x3, minggu 3: y = 8,746 - 0,0019x + (4,3E-06)x2 + (-4E-09)x3, minggu 4: y = 9,015 - 0,0018x + (5E-06)x2 + (-1,1E-08)x3. Fungsi karakteristik arus keluaran minggu 1: y = 2,5006 + (-9,8E-04)x + (5,1E-0,6)x2 + (-1,1E-08)x3, minggu 2: y = 2,5422 + (-3,7E-04)x + (1,5E-06)x2 + (-7E-09)x3, minggu 3: y = 2,537 + (-1,7E-03)x + (1,4E-05)x2 + (-4,0E-08)x3, minggu 4: y = 2,657 - 0,0010x + (7,1E-06)x2 + (-2,2E-08)x3. Kata kunci: nano, nanopartikel perak, aki maintenance free bekas, pola tegangan keluaran, pola arus keluaran, pengaruh nanopartikel perak terhadap tegangan dan arus keluaran aki maintenance free bekas Abstract This study aims to i) find out the pattern of the output voltage in the used maintenance free accumulator which is added by silver nanoparticles in a closed circuit, ii) find out the output electric current pattern of the maintenance free accumulator which is added by silver nanoparticles in a closed circuit. This study began by making silver nanoparticles in the form of 3 mM AgNO3 solution for each study. Next, testing the absorbance characteristics of silver nanoparticles solution by UV-Vis Spectrophotometer. Then, 3 mL of silver nanoparticle solution with an absorbance value of 3.187 was added to the used maintenance free accumulator. Measurement of the output voltage and electric current of the used maintenance free accumulator is carried out for 240 minutes with the use of 2 LED lights. The results of this research are presented in graphical form which is then analyzed using Origin fitting to find the function of the output voltage and electric current of the free maintenance free accumulator. Based on the results obtained, the output voltage and current pattern of maintenance free batteries plus 3 mM silver nanoparticles are in the form of an order polynomial function 3. The output voltage characteristic function is week 1: y = 8,507 + 0,0021x + (1,01E-05)x2 + (-2,1E-08)x3, week 2: y = 8,694 - 0,0013x + (5,6E-06)x 2 + (-1,8E-08)x3, week 3: y = 8,746 - 0,0019x + (4,3E-06)x2 + (-4E-09)x3, week 4: y = 9,015 - 0,0018x + (5E-06)x2 + (-1,1E-08)x3. The output electric current characteristic function is week 1: y = 2,5006 + (-9,8E-04)x + (5,1E-0,6)x2 + (-1,1E-08)x3, week 2: y = 2,5422 + (-3,7E-04)x + (1,5E-06)x2 + (-7E-09)x3, week 3: y = 2,537 + (-1,7E-03)x + (1,4E-05)x2 + (-4,0E-08)x3, week 4: y = 2,657 - 0,0010x + (7,1E-06)x2 + (-2,2E-08)x3. Keywords: nano, silver nanoparticles, used maintence free accumulator, the effect of nanosilver toward the output voltage and electric current